Blueberry as an Attractive Functional Fruit to Prevent (Pre)Diabetes Progression - Nunes, Sara (2021)
Prediabetes, a subclinical impairment between euglycemia and hyperglycemia, is a risk factor for the development of type 2 diabetes mellitus (T2DM) and associated micro-and macrovascular complications. Lifestyle therapy, the first-line treatment of prediabetes, includes physical exercise and dietary regimens enriched in phytochemicals with health-related properties. Blueberries (Vaccinium spp.), given their pleasant taste and great abundance in beneficial phytochemicals, have gained public interest all over the world. Along with a high antioxidant activity, this functional fruit is also well-recognized due to its hypoglycemic and insulin-sensitizing effects and has been recommended for overt T2DM management. Yet blueberries target several other pathophysiological traits, namely gut microbiota dysbiosis and hepatic dysmetabolism, that ensue when prediabetes begins and for which pharmacological interventions tend to be delayed. In this work, we revisited preclinical data from in vitro assays, animal models and human studies, aiming to disclose the potential mechanisms by which blueberries may be a fruitful source of phytochemicals able to prevent (pre)diabetes progression. Collectively, future efforts should focus on longer-term studies with standardized interventions and readouts, particularly in humans, that will hopefully bring more robust evidence and concrete guidance for blueberries’ effective use in prediabetes. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.